Additive manufacturing and postprocessing of Ti-6Al-4V for superior mechanical properties. (10th October 2016) - Qian, M.; Xu, W.; Brandt, M.; Tang, H.P.
Abstract: Abstract : The capabilities of metal additive manufacturing (AM) are evolving rapidly thanks to both increasing industry demand and improved scientific understanding of the process. This article provides an overview of AM of the Ti-6Al-4V alloy, which has essentially been used as a yardstick to gauge the capability of each metal AM process developed to date. It begins by summarizing the metal AM processes existing today. This is followed by a discussion of the macro- and microstructural characteristics, defects, and tensile and fatigue properties of AM Ti-6Al-4V by selective laser melting, laser metal deposition (both powder and wire), and selective electron-beam melting compared to non-AM Ti-6Al-4V. The tensile and fatigue properties of as-built AM Ti-6Al-4V (with machined or polished surfaces) can be made comparable, or even superior, to those of Ti-6Al-4V in the most commonly used mill-annealed condition. However, these properties can exhibit a large degree of scatter and are often anisotropic, affected by AM build orientations. Post-AM surface treatments or both the post-AM surface and heat treatments are necessary to ensure the minimum required properties and performance consistency. Future directions to further unlock the potential of AM of Ti-6Al-4V for superior and consistent mechanical properties are also discussed.